Estrategia de comunicación popular: vinculación de la escuela “Mujeres de Frente” para la socialización de procesos de educación popular y feminista. - Cárdenas Zapata, Stephany Pamela (2014)
The research presented a communication issue from the perspective of gender , popular and alternative communication in building popular communication strategies for linking school " Women's Front" for the socialization process of popular education and feminist . The work of an exploration of the different theories that arise throughout the history of communication , with special emphasis on those that are at our Latin American context by several authors thoughts of taking as a starting point diversity realities and situations that are typical of the countries on our continent. The study on gender communication and women's movements are part of the second chapter which details the birth and development of the processes in women's organizations and what their conceptions , challenges and proposals for the construction of gender are means and visibility they have on the overall social environment.